2009
DOI: 10.1007/s10646-009-0311-8
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of paraquat on photosynthesis and the response to oxidative stress in Chlorella vulgaris

Abstract: This study investigated the effects of paraquat, a widely used herbicide, on the aquatic unicellular alga Chlorella vulgaris through short-term toxicity tests at the physiological and gene transcriptional levels. Exposure to 0.5 microM paraquat increased the activities of the antioxidant enzymes superoxide dismutase, peroxidase, and catalase to levels 4.93, 3.19, and 3.09 times higher, respectively, than those of the control. Furthermore, exposure to 0.75 microM paraquat increased the activities of these antio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 33 publications
2
42
0
2
Order By: Relevance
“…The high toxicity of this compound has also been observed in studies involving the use of bacteria, small crustaceans, algae and aquatic plants. [8][9][10][11][12] Thus, its presence in the environment can cause adverse effects in aquatic and terrestrial organisms. Therefore, it is desirable for the development and optimization of viable technologies with a focus on disposal of such waste.…”
Section: Introductionmentioning
confidence: 99%
“…The high toxicity of this compound has also been observed in studies involving the use of bacteria, small crustaceans, algae and aquatic plants. [8][9][10][11][12] Thus, its presence in the environment can cause adverse effects in aquatic and terrestrial organisms. Therefore, it is desirable for the development and optimization of viable technologies with a focus on disposal of such waste.…”
Section: Introductionmentioning
confidence: 99%
“…Among different herbicides, Paraquat (1,1'-dimethyl-4,4'-bipyridinium, PQ) is the most widely used herbicide in the world because of its greater efficiency and low cost (Qian et al 2009a;Moran et al 2010). It blocks photosynthesis by accepting electrons from photosystem I (PSI) and causes overproduction of reactive oxygen species (ROS) which caused alteration of the main biomolecule classes, leads to structural and func-1120 A.…”
Section: Introductionmentioning
confidence: 99%
“…It blocks photosynthesis by accepting electrons from photosystem I (PSI) and causes overproduction of reactive oxygen species (ROS) which caused alteration of the main biomolecule classes, leads to structural and func-1120 A. Sood et al tional changes in lipids, proteins, chlorophylls, and nucleic acids (Qian et al 2009a;Moran et al 2010;Sood et al 2011). Holst et al (1982 observed that bipyridilium and phenolic herbicides were detrimental to A. mexicana, causing up to 75% reduction in N 2 fixation.…”
Section: Introductionmentioning
confidence: 99%
“…Sun et al (2006) reported that phenanthrene rapidly accumulated in fish tissue and stimulated the production of free radicals in the liver of Carassius auratus. All of these are examples of the oxidative stress that may be induced by xenobiotics (Shi et al 2005;Qian et al 2009). However, limited studies have been undertaken concerning the production of ROS and the resulting oxidative stresses in aquatic plants in the presence of phenanthrene exposure.…”
Section: Discussionmentioning
confidence: 99%